2013
DOI: 10.1038/lsa.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Label-free super-resolution imaging of adenoviruses by submerged microsphere optical nanoscopy

Abstract: Because of the small sizes of most viruses (typically 5-150 nm), standard optical microscopes, which have an optical diffraction limit of 200 nm, are not generally suitable for their direct observation. Electron microscopes usually require specimens to be placed under vacuum conditions, thus making them unsuitable for imaging live biological specimens in liquid environments. Indirect optical imaging of viruses has been made possible by the use of fluorescence optical microscopy that relies on the stimulated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
189
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(196 citation statements)
references
References 28 publications
1
189
0
1
Order By: Relevance
“…Such an object can be viewed through what is known as phase contrast microscopy [29]. Imaging of phase objects is especially important for biological systems [27,41]. The following optical system described in Fig.…”
Section: :405mentioning
confidence: 99%
See 1 more Smart Citation
“…Such an object can be viewed through what is known as phase contrast microscopy [29]. Imaging of phase objects is especially important for biological systems [27,41]. The following optical system described in Fig.…”
Section: :405mentioning
confidence: 99%
“…Microsphere near-field nano-structures were observed and analyzed using picosecond pulses [26]. Viruses were observed by microsphere optical nanoscopy [27]. It has been shown that it is possible to control the focusing properties of the microsphere by using pupil masks [28].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported the observation of a gold-coated anodic aluminum oxide membrane by SiO 2 microspheres with refractive index (n) of 1.46 (2”m<diameter<9”m) and pushed the lateral resolution to 50 nm (λ/14 at λ = 750 nm) [18]. Observations of subcellular structures like centrioles, mitochondria, chromosomes [22] and 75-nm adenoviruses [24] have also been demonstrated by this microsphere based super-lens. Researchers have also proved that the super-resolution capability of microsphere can be enhanced by semi-immersing microspheres in liquid [25].…”
Section: Introductionmentioning
confidence: 90%
“…In the past few years, studies have shown that dielectrics with specific morphology have the capability to provide image resolution beyond diffraction limit [17][18][19][20][21][22][23][24]. Lee et al demonstrated that high resolution imaging, i.e., λ/2.2 (λ = 472nm), can be obtained by nanoscale dielectric plano-spherical convex lenses due to the curvilinear trajectories of light that induced significantly short near-field focal lengths [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, optical microscopic imaging resolution has a theoretical limit of approximately 200 nm within the visible-light spectrum because of the far-field diffraction limit, which prevents the technique from being used to directly observe nano-objects 23 . If individual ultralong nanotubes can be observed under an optical microscope through a facile and reversible method, nanotube characterization and manipulation will tremendously benefit its fundamental investigations and various specific applications.…”
Section: Introductionmentioning
confidence: 99%